Blends of neem oil based polyesteramide as nanofiber mats to control Culicidae. Issue 70 (25th November 2020) - Konchada, Sravanya; Killi, Naresh; Sayyad, Shahebaz; Gathalkar, Ganesh B.; Gundloori, Rathna V. N.
Abstract : Electrospun nanofiber mats immobilized with transfluthrin to control mosquitoes. Abstract : Mosquitoes act as vectors for several disease-causing microorganisms and pose a threat to mankind by transmitting various diseases. There are different conventional methods to repel or kill these mosquitoes for avoiding susceptibility against infections. However, to overcome the difficulties with conventional methods, new advanced materials are being studied. For the first time, we report developing a nanofiber mat with a controlled release of insecticide to repel or detain the mosquitoes. Briefly, various blend compositions were prepared by manipulating the ratio of neem oil-based polyesteramide (PEA) and polycaprolactone (PCL) immobilized with insecticide, transfluthrin (Tf). The blend solutions were electrospun to get non-woven nanofiber mats, and these nanomaterials were characterized by various spectroscopic techniques to understand their physicochemical properties. The surface morphology was analyzed using environmental scanning electron microscopy (E-SEM), and the diameter of the nanofibers was in the range of 200 to 450 nm. Further, thermal and mechanical properties were evaluated to understand the stability of nanofiber mats. In vitro drug release studies of nanofiber mat PPT-1335 showed controlled and sustained release of Tf, with ∼35% of Tf released in 24 h. However, a film of the same composition (PPT-1335) showed ∼5% of Tf release within 24 h. Moreover, in vivo bio-efficacy studies suggested the mortality of mosquitoes was about 50% with PP-133, which was further increased to 100% within 12 h in the presence of Tf (PPT-1335). However, 60% mortality of mosquitoes was observed with the film of PPT-1335. Hence, the nanofiber mat showed better efficacy against mosquitoes as compared to the film of the same composition. The degradation studies under various conditions revealed biocompatibility of the developed nanofiber mats with the ecosystem.